Pertanggungjawaban Hukum Ultimate Beneficiary Owner (UBN) yang Melakukan Gratifikasi Terhadap Pejabat: Studi Kasus Putusan Mahkamah Agung Nomor 2205K/Pid.Sus/2022 - Isti Puspitasari; Erviyanti Rosmaida; Taufiqurrohman Syahruri (Jurnal Relasi Publik, 2024)
Decision Number 2205 K/Pd/Sus/2022 The Supreme Court again upheld the acquittal decision of Samin Tan as the owner of PT Beneficial Ownershiprneo Lumbung Energi & Metal (PT BLEM). The panel is of the opinion that the giver of gratification cannot be punished because the Corruption Eradication Law is not designed to punish the giver of gratification even though Samin Tan's position as the giver of gratification is the ultimate beneficiary owner of PT BLEM. The research method used in this research is using normative juridical research methods and using literature study techniques to answer the problems in this research. The result of the discussion of the first problem formulation is that Samin Tan cannot be held criminally responsible because the person giving the gratification is not criminalized under the law even though Samin Tan is the ultimate beneficiary owner who has the potential to commit this act because it is in the interests of his company. The result of the discussion on the formulation of the second problem is that the judge's considerations in the decision did not prioritize a sense of justice and expediency because they only prioritized legal certainty which resulted in Samin Tan being able to escape the demands of the public prosecutor.